Znaczenie postaw wobec kulturowych ról płci, rodzinnego wzorca pracy matek oraz podziału obowiązków domowych i rodzicielskich dla zatrudnienia matek małych dzieci w Polsce - Kocot-Górecka, Katarzyna; Kurowska, Anna (Studia Demograficzne, 2013)
The paper presents estimation results of a logistic regression developed in order to explore such predictors of employment of mothers with children up to 14 years old in Poland as maternal attitudes towards cultural gender roles, a parental family of a working mother and sharing household and childcare duties between parents. The analysis was based on the data from the first wave of the Generations and Gender Survey (GGS-PL1). It was found that the family pattern of a working mother significantly increased the chances of employment of her daughter having her own offspring. Egalitarian attitudes towards gender roles have not proved to be a significant predictor of maternal employment. However, the stronger mother’s approval of the statement that “a small child suffers when his/her mother works” was, the lower the likelihood was of her employment. A larger number of children turned out to be a stimulus for maternal employment when the division of responsibilities between partners and the extent of informal childcare use were controlled for in the model.